A cross-sectional study on the relationship between foot structure and foot function in children - Chen, Yuxin. (2013)
The foot arch of children develops rapidly during the first decade of life. Both flexible flatfoot and hypermobility can be due to developmental profiles. Many parents believed that flatfoot in children can cause gait disorders in future and treatment is needed. But relationship has not been scientifically proven. This study investigates the relationship between the foot structure and the function foot of children. It is hypothesized that this relationship is insignificant.